PERJUANGAN TOKOH UTAMA DALAM CERPEN JALAN BUNTU KARYA RAUDHATUL TASSYA KHAIRUNISA: ANALISIS STRUKTUR BURHAN NURGIYANTORO - Wulandari, Elsa; Nuranggraini, Indri; Budiyanto, Diva Amelia; Fadhilla, Indah (Universitas Hamzanwadi, 2024)
This study aims to analyze the main themes in the story, such as the struggle for justice, assertiveness, and honesty, as well as to understand the internal conflict experienced by the main character, Nara, and her interactions with other characters such as her mother and the police. The data collection technique was conducted through literary text analysis, in which the data found were identified and recorded. This study aims to identify and analyze the theme of the struggle in seeking justice for the main character in the short story Jalan Buntu, understand internal conflicts, examine moral and social values through intrinsic elements. The method of analysis used is descriptive qualitative, with analysis of the theory and assessment of fiction according to Burhan Nurgiyantoro. The data analyzed includes the definition of intrinsic elements, important quotes from the story, and analysis of each quote of events in the story. This study reveals that the story 'Jalan Buntu' shows the depiction of a brave and firm character in upholding justice. Despite facing many obstacles and pressures, Nara remains firm on the principles of justice and refuses to settle unfair cases, reflecting strong values of honesty and justice. Based on the results of the analysis of the short story Jalan Buntu, it shows that Nara, as the main character, fights for justice despite facing various obstacles, rejects unfair settlement offers, and reflects the values of honesty and courage.